2013
DOI: 10.1016/j.neuron.2013.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition-Induced Theta Resonance in Cortical Circuits

Abstract: Both circuit and single-cell properties contribute to network rhythms. In vitro, pyramidal cells exhibit theta-band membrane potential (subthreshold) resonance, but whether and how sub-threshold resonance translates into spiking resonance in behaving animals is unknown. Here, we used optogenetic activation to trigger spiking in pyramidal cells or parvalbumin immunoreactive interneurons (PV) in the hippocampus and neocortex of freely-behaving rodents. Individual directly-activated pyramidal cells exhibited narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
331
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 307 publications
(369 citation statements)
references
References 63 publications
(98 reference statements)
35
331
3
Order By: Relevance
“…Light stimulation (50-to 70-ms light pulses) was applied on every shank separately during spontaneous behavior in the home cage (n = 4 mice) or during urethane anesthesia (n = 6 mice; ref. 49). Offline, spikes were sorted and classified as putatitve PYR or INT using a Gaussian mixture model (49).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light stimulation (50-to 70-ms light pulses) was applied on every shank separately during spontaneous behavior in the home cage (n = 4 mice) or during urethane anesthesia (n = 6 mice; ref. 49). Offline, spikes were sorted and classified as putatitve PYR or INT using a Gaussian mixture model (49).…”
Section: Methodsmentioning
confidence: 99%
“…49). Offline, spikes were sorted and classified as putatitve PYR or INT using a Gaussian mixture model (49). Spike sequences were detected and compared using a cross-validated template method or an alternate pair-wise method; statistical significance was verified by resampling (permutation test).…”
Section: Methodsmentioning
confidence: 99%
“…Optogenetic manipulation of PV + interneuron activity showed that they are necessary and sufficient for the generation of network oscillations in both hippocampus and neocortex. Stimulation of PV + cells at theta frequency induces theta spike resonance in CA1 pyramidal cells (99), and stimulation of PV + cells at gamma frequency leads to gamma oscillations in the local field potential in somatosensory cortex (11)(12). Conversely, suppression of PV + cells reduces gamma oscillations (12).…”
Section: Role Of Pvmentioning
confidence: 99%
“…In attempts to manipulate the activity of interneurons by selectively knocking out different subunits of glutamatergic and GABAergic receptors in interneurons, alterations in hippocampal theta, gamma, and ripple oscillations have been found [18][19][20][21]. Cell type-specific manipulations based on optogenetics have on the other hand provided in vivo evidence that GABAergic interneurons control oscillatory activity in hippocampal PCs, as shown by changes in theta [22,23] and ripple rhythms [24]. In this study, we made whole-cell recordings on CA1 neurons of a completely isolated hippocampus, in which slow oscillations could be generated intrinsically in hippocampal neurons, to investigate the contribution of GABAergic interneurons to hippocampal generation of neuronal oscillation.…”
Section: Introductionmentioning
confidence: 99%